2007
DOI: 10.1116/1.2752513
|View full text |Cite
|
Sign up to set email alerts
|

Growth of carbon nanotubes with resist-assisted patterning process

Abstract: The authors developed a growth method for carbon nanotubes (CNTs) by using a resist-assisted patterning process. The CNTs can be grown directly on the patterned catalyst surface without a diffusion barrier. The growth-site patterns were fabricated on a nickel/silicon (Ni∕Si) substrate by a conventional lithography method using a photopatternable resist. The growth mechanism of the CNTs without diffusion barrier was confirmed by Raman spectroscopy and transmission-electron microscope measurement. The carbon-net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…Allowing reasonable margins for parameters such as electron-transmission rate, and incident light, a proposed standard PEC is approximately 2 A. In our previous studies, we confirmed enhanced and stable electron emission with RAP grown CNTs [15,16]. Hence, CNTs as electron sources are thought to be one of the best candidates for driving selenium based practical sensors.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Allowing reasonable margins for parameters such as electron-transmission rate, and incident light, a proposed standard PEC is approximately 2 A. In our previous studies, we confirmed enhanced and stable electron emission with RAP grown CNTs [15,16]. Hence, CNTs as electron sources are thought to be one of the best candidates for driving selenium based practical sensors.…”
Section: Introductionsupporting
confidence: 62%
“…The reactive gases, C 2 H 2 and NH 3 , with a constant gas flow rate ratio, were maintained at a process pressure of 6.5 × 10 −2 Pa for 5 min. The growth temperature was 580 • C. More detailed process conditions for the RAP process were reported previously [15].…”
Section: Methodsmentioning
confidence: 99%
“…The initial CNTs without post-treatment are vertically aligned and formed several nickel catalysts on top of multiwall CNTs [7]. However, after post-treatments, there is no nickel catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…CNT emitter arrays were grown with a resist-assisted pattering (RAP) process without a diffusion barrier using triode plasma enhanced chemical vapor deposition (PE-CVD) technique [9,10]. The CNT growth was performed with a pressure of 2.0 Torr at temperature of 800 o C in a 40:60 mixture of acetylene (C 2 H 2 ) and ammonia (NH 3 ), respectively.…”
Section: Methodsmentioning
confidence: 99%